An immune receptor complex evolved in soybean to perceive a polymorphic bacterial flagellin - Yali Wei (Nature Portfolio, 2020)
Ralstonia solanacearum evades plant immunity by producing an atypical flagellin protein, thus causing bacterial wilt disease. Here, Wei et al. show that soybean has evolved a divergent flagellin receptor that recognises R. solanacearum flagellin and enhances wilt resistance when transferred to other plants.